THE INTENTION TO REVISIT MALAYSIAN TOURISM IN THE POST COVID-19 PERIOD (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
Within the unprecedented situation, Malaysian rural tourism was badly hit by the COVID-19 outbreak that reverberated across the global economy. This study represents the interdependency of revisit intention that correlated with rural tourism stigma and trust to excess the COVID-19 preventive efforts in uplifting the rural tourism in the country. As Malaysian daily COVID-19 cases are under control starting from November 2021, it is the appropriate time to study on the intention to revisit. Theory of planned behavior was applied to define the likelihood of tourists revisiting the rural tourism destination after COVID-19 or in the future. Results indicate that the current development of pandemic arises the concern among tourists and influences their trust to revisit. 298 responses analyses to examined to impede meaningful investigation for regional planning and remote area tourism development from the views of stakeholders, the planning agencies, and communities. The result of the study has shown that attitude, fear of COVID-19, and compliance have a positive and significant influence on trust. Likewise, trust has a positive and significant influence on intention, while compliance has the strongest influence on trust. Hence, this study is essential to highlight factors hampering the COVID-19 pandemic on rural tourism in Malaysia.
Keywords: revisit intention; rural tourism; revisit intention, rural tourism; post-Covid-19, pandemic; pandemic; Theory of Planned Behaviour (TPB)